Topical knowledge in L2 speaking assessment: Comparing independent and integrated speaking test tasks. (January 2018) - Huang, Heng-Tsung Danny; Hung, Shao-Ting Alan; Plakans, Lia
Integrated speaking test tasks (integrated tasks) provide reading and/or listening input to serve as the basis for test-takers to formulate their oral responses. This study examined the influence of topical knowledge on integrated speaking test performance and compared independent speaking test performance and integrated speaking test performance in terms of how each was related to topical knowledge. The researchers derived four integrated tasks from TOEFL iBT preparation materials, developed four independent speaking test tasks (independent tasks), and validated four topical knowledge tests (TKTs) on a group of 421 EFL learners. For the main study, they invited another 352 students to respond to the TKTs and to perform two independent tasks and two integrated tasks. Half of the test takers took the independent tasks and integrated tasks on one topic combination while the other half took tasks on another topic combination. Data analysis, drawing on a series of path analyses, led to two major findings. First, topical knowledge significantly impacted integrated speaking test performance in both topic combinations. Second, the impact of topical knowledge on the two types of speaking test performances was topic dependent. Implications are proposed in light of these findings.